The Effects of Negative Air Ions upon Some Biochemical Parameters in Rats - Kose, HAYRULLAH; KÖSE, HAYRULLAH; Seyrek, Kamil; Kiral, Funda (My University, 2010)
Negative air ions (NAI) are capable of evoking a wide range of responses in bacteria, protozoa, higher plants, insects and animals, as well as in humans. However, their precise mechanism of action is uncertain. There is evidence to show that NAI are able to influence mood, behaviour, and performance of certain tasks. In this study, rats were put into two groups, a control and an experimental group. Animals in the experimental group were exposed to an atmosphere enriched with NAI for four weeks. At the end of the experiment, we determined the blood glutathione (GSH), malondialdehyde (MDA), ceruloplasmin, hemoglobin and packed cell volume (PCV) concentrations of the rats. MDA concentrations in the experimental group were lower than that of the control animals (4.02 mu mol/l and 5.11 mu mol/l, respectively). Likewise, in the experimental animals, ceruloplasmin levels were also reduced from 33.18 mg/dl to 26.27 mg/dl, whereas no alterations in hemoglobin or glutathione concentrations were detected. An increase from 43.80% to 46.10 % was shown in the PCV content of the experimental rats. In addition, the mean weight gain of the experimental group was less than that of the control group. However, in terms of these parameters, we were unable to detect any significant differences between the two groups. In conclusion, contrary to some in vitro studies, this in vivo animal study suggests that NAI has limited or no effect upon certain biochemical parameters.